Two new genera of Apocynaceae for Laos - Rodda, Michele (Thai Forest Bulletin (Botany), 2020)
Examination of unidentified Apocynaceae specimens at QBG and SING lead to the discovery of one specimen of Meladerma deciduum and two specimens of Harmandiella cordifolia from Laos. Harmandiella was earlier considered endemic to Thailand and Vietnam while Meladerma was earlier reported from Thailand and Peninsular Malaysia. Harmandiella cordifolia and Meladerma deciduum are typified.